Current Views on the Relationship Between Cognitive Information Status and Sentence Structure - Kalėdaitė, Violeta (Kalbotyra, 2003)
Over the past several decades a vast body of literature has emerged investigating the native speaker’s implicit ability to assess the appropriateness of a grammatical sentence in a particular context. The present paper attempts to examine some of the most influential approaches that address the question of how cognitive and pragmatic factors correlate with constituent order. In a field where so much literature has been written there is an urgent need to be very selective; the paper therefore focuses on very general tendencies, facts and assumptions that relate to the vast area of the present discussion.